Immunohitochemical expression of Bcl-2in human colocrectal carcinoma - AbdulGhafour, Kifah H.; Hassan AL-Tai, Tharwa H.; shaker, Hind H. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Colorectal carcinoma is the most frequent type of malignancy in terms of incidence,it is the third most common cancer world wide in both sexes . bcl_2 expression has been described as been a better prognostic factor in colorectal carcinoma. Objcetives: To determine the frequency and the pattern of Bcl-2 expression in colorectal carcinoma by immunohistochemical technique and to correlate this expression with different clinicopathological parameters. Material and method: Thirty cases of colorectal carcinoma were studied, these cases were diagnosed in private laboratories in Baghdad / Iraq from January 2015 to Juan 2015. Clinicopathological parameter such as age, gender , pathological diagnosis , tumor site , lymph nodes status , grade and stage of tumor were collected from patients files..Sections of 4μm were stained by hematoxylen and eosin stain, and immunohistochemical stained for Bcl-2. Results: Nineteen (63.3%) cases were males, 11(36.7%) cases were females, with age distribution ranging from (39-89) years with a mean age of 56.5 years. Histologically the tumor grade range from moderately differentiated in 27 (90%) cases and poorly differentiated in 3 (10%) cases. Ten (33.3%)cases located in the right colon and sigmoid each 6(20%) cases in rectum,8(26.7%) cases in the cecum,3(10%)cases located in right colon and sigmoid each,6(20%) cases in the rectum and 8(26.7%) cases in the left colon. Regarding pathological staging (TNM system),2 (6.7%) cases were stage T2 ,24 (80%) were stage T3 ,4(13.3%) cases were T4. Lymph node involvement found in 14(46%) cases and distant metastasis was found in 9(30%) cases. Bcl-2 expression was present in 14(46.7 %) cases of 30 colorectal carcinoma.There was no significant correlation with age, sex, histopathological grade, location, lymph nodes status and tumor invation. Conclusion: There was no significant statistical correlation between bcl expression by tumor cell of colorectal carcinoma and different clinicopathological parameters in this study.